Pre-examination and triage management of dental clinic in the general hospital during the normalization prevention and control of COVID-19 epidemic (新型冠状病毒肺炎疫情常态化防控期间综合医院口腔门诊预检分诊管理) - XIONG Yanjie (熊雁洁); LIU Fang (刘芳); HUANG Zhouyan (黄周燕); WANG Chao (王超) (中西医结合护理)
Objective To investigate pre-examination and triage managements of outpatient of the dental clinic in general hospitals during the normalization prevention and control of COVID-19 epidemic. Methods According to the relevant guidelines for epidemic prevention and control, combined with the situation of dental clinic, a series of management plans for pre-examination and triage were developed, and the changes of outpatient distribution were analyzed statistically. Results From June to August 2020, the total number of outpatients in dental clinic was 3821, among whom, 3776 (98. 82%) patients had normal temperature and their epidemiological questionnaire were negative. No suspected or confirmed COVID-19 patients were appeared, and no emergency management plan was carried out in the dental clinic. Conclusion The management plan of pre-examination and triage management in dental clinic, based on epidemiological investigation and risk classification of dental treatment, was conducive to screening high-risk patients, and improve efficiency. (目的 探讨新型冠状病毒肺炎疫情常态化防控期间综合医院口腔科门诊预检分诊管理方案实施效果。方法 根据国家及市级卫健委、中华口腔医学会等相关疫情防控指导文件, 结合科室情况, 制定一系列口腔科预检分诊管理方案并实施, 观察实施效果。结果 2020年6月—8月安全有序接诊3821名口腔门诊患者, 无疑似或新冠肺炎患者, 未启动口腔科应急管理预案, 未发生诊室交叉感染事件。结论 新冠肺炎疫情期间口腔科实施预检分诊管理方案, 基于流行病学调查登记和口腔诊疗风险分类, 有利于筛查高风险就诊患者, 在保护医患双方的前提下, 最大限度安全有序地恢复口腔门诊诊疗秩序, 为患者提供口腔诊疗服务。)